Grating Lobe and Sidelobe Suppression of Frequency Jump Burst based on Improved Multi-Objective Gray Wolf Optimization Algorithm - Liang, Shuo; Tang, Chunrui; Ye, Fang; Li, Yibing; Jiang, Tao (2022 International Conference on Microwave and Millimeter Wave Technology (ICMMT), 2022)
Frequency jump burst (FJB) signal combines the characteristics of linear frequency modulation (LFM) signal and frequency stepping signal. It can effectively achieve high range resolution without increasing system cost and complexity. Due to the fixed step frequency in the FJB, the autocorrelation function (ACF) has a set of periodic peaks, which is called grating lobes. The side lobe and the grating lobe may hide small targets and weak reflection target. In this paper, the improved Multi-Objective Gray Wolf Optimization (IMOGWO) algorithm was applied to jointly suppress the side lobe and grating lobe. The instantaneous bandwidth of radar is limited. By changing the number of subpulses and step frequency, this paper analyzed the convergence and diversity of the pareto front, proved that it is very effective to design parameters of frequency jump transmission signal in using IMOGWO algorithm.